1994
DOI: 10.1126/science.265.5180.1839
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Aluminophosphate Molecular Sieve Crystals Grown at Inorganic-Organic Interfaces

Abstract: Tubular aluminophosphate molecular sieve crystals were grown at an organic interface with their channels (7 angstroms in cross section) vertical to the substrate. To induce surface nucleation and oriented growth of AIPO4-5 crystals, organophosphonate layers cross-linked with Zr(lV) were assembled on a gold substrate and the modified substrate was immersed in a hydrothermal bath containing reagents for the synthesis of the molecular sieve. Reflection-absorption infrared studies demonstrated the stability of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(88 citation statements)
references
References 26 publications
(16 reference statements)
2
84
0
1
Order By: Relevance
“…1 shows XRD patterns of as-synthesized AlPO 4 -5, calcined AlPO 4 -5 and 0.4 % Rh loaded AlPO 4 -5. The XRD patterns of these samples correspond well with that for reported AlPO 4 -5 structure and do not show any impurity [21][22][23][24][25][26]. Upon calcination, a little increase in intensities of XRD patterns were observed due to little increased particle size.…”
Section: Resultssupporting
confidence: 70%
“…1 shows XRD patterns of as-synthesized AlPO 4 -5, calcined AlPO 4 -5 and 0.4 % Rh loaded AlPO 4 -5. The XRD patterns of these samples correspond well with that for reported AlPO 4 -5 structure and do not show any impurity [21][22][23][24][25][26]. Upon calcination, a little increase in intensities of XRD patterns were observed due to little increased particle size.…”
Section: Resultssupporting
confidence: 70%
“…[26] The orientation of AEL molecular sieve membranes could be modified by adjusting the addition of HF. AEL consists of ten-membered-ring channels parallel to the c axis of the crystal, which is the fastest growing axis during the ionothermal procedure.…”
mentioning
confidence: 99%
“…They have demonstrated the high molecular selectivity of chemical sensors based on this method. The same authors discovered [87,88] that single component organophosphonate films could promote the growth of oriented molecular sieves, specifically zincphosphate and aluminophosphate crystals. It was found that the surface crystallization requires only very small aggregates of phosphate groups.…”
Section: Zeolite Films On Metallic Supportsmentioning
confidence: 90%